Anterior lamina cribrosa insertion in primary open-angle glaucoma patients and healthy subjects. - Kyoung Min Lee (PLoS ONE, 2014)
PURPOSE:To determine using swept-source optical coherence tomography (SS-OCT) whether there are differences in the location of the anterior lamina cribrosa insertion (ALI) in primary open-angle glaucoma (POAG) patients and healthy subjects. METHODS:Fifty three eyes from 53 patients with POAG, and 53 eyes from 53 age-matched healthy subjects were included prospectively in Seoul National University Bundang Hospital. Twelve radial line B-scans centered on the optic disc in every half-clock-hour meridian were acquired using SS-OCT. The ALI position was assessed by measuring two parameters: (1) ALI distance (ALID)--the distance from the anterior scleral canal opening (ASCO) to the ALI; and (2) marginal anterior lamina cribrosa surface depth (mALCSD)--the perpendicular distance from the ASCO plane to the anterior lamina cribrosa surface. These parameters were compared between the two groups for each meridian. RESULTS:Both ALID (256 ± 54 vs. 209 ± 37 µm, mean ± SD, p < 0.001) and mALCSD (232 ± 63 vs. 187 ± 40 µm, p < 0.001) were significantly greater in the POAG group than in the normal group. The largest difference was observed at the 6.5 o'clock and 11.5 o'clock meridians for both ALID and mALCSD. Multiple regression analysis revealed a negative correlation between age and both ALID and mALCSD in the control group, and a negative correlation between mean deviation of the visual field test and both ALID and mALCSD in the POAG group. CONCLUSIONS:The ALI was displaced posteriorly in eyes with POAG compared to those of healthy controls. This finding suggests that the posteriorly located lamina cribrosa insertion is an important component of glaucomatous optic nerve excavation.